Exercise Training for Cardiac Patients, Why and How to Prescribe It? - Carré, François (Aktuelle Kardiologie, 2020)
The benefits of regular physical activity whether in primary- or secondary prevention of cardiovascular disease are now irrefutable. Despite its well proven benefits, exercise training remains underused because of lack of insight and familiarity of the majority of cardiologists. This review offers cardiologists the necessary informations about the pathophysiological mechanisms, effects and limitations of the predominantly used training methods in various kardiovascular diseases.
Keywords: physical activity; exercise training; cardiovascular disease; cardiac rehabilitation; primary secondary prevention